Procalcitonin‐guided antibiotic therapy in AECOPD patients: Overview of systematic reviews. (23rd March 2021) - Di, Jiaqi; Li, Xuanlin; Xie, Yang; Yang, Shuguang; Yu, Xueqing
Abstract: Background: Procalcitonin (PCT)‐guided antibiotic therapy has emerged as mainstream treatment for acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and has been studied in many systematic reviews (SRs), but robust conclusion has not been drawn. Thus, this overview aims to summarize and critically evaluate the methodological and evidence quality of SRs on this topic. Methods: PubMed, EMBASE, Cochrane library, and Web of science were searched for SRs regarding on PCT‐guided antibiotic therapy on AECOPD. Two reviewers assessed the quality of SRs in line with AMSTAR‐2 tool and evaluated the strength of evidence quality with the grading of recommendations, assessment, development, and evaluation (GRADE) system for concerned outcomes independently. Results: Six SRs were published from Jun 2011 to Aug 2019, with from 4 (556 patients) to 15 (2571 patients) randomized controlled trials (RCTs) and retrospective studies. All the included SRs were classified as critical low methodology quality according to A MeaSurement Tool to Assess Systematic Reviews 2 (AMSTAR‐2) tool. Most of SRs were absented a list of excluded studies (item 7), and adequate investigation of publication bias and discuss its likely impact on the results (item 15). The PCT‐guided antibiotic therapy may reduce antibiotic exposure days and antibiotic prescription rate in patients with AECOPD without affecting treatment success rate or causing adverse events (all‐cause mortality, re‐admission, re‐exacerbation), but the results should be study deeper for the low or moderate evidence quality. Conclusion: Current SRs show that PCT‐guided antibiotic therapy could be employed by clinicians in treatment of AECOPD. However, the high‐quality evidence of outcomes is lacking, further intensive exploration should be carried out on the precise role of PCT‐guided antibiotic therapy on AECOPD.